irMass TransferDuring the Pre-Usage Dehydration of PolyvinylAlcohol Hydrogel Wound Dressings: Mass transfer during pre-usage dehydration of PVPhydrogels - Sirousazara, Mohammad; Kokabi, Mehrdad; Yari, Morteza (Iranian Journal of Pharmaceutical Sciences, 2008)
Nowadays, hydrogels are widely used as wound dressings in biomedicalapplications. Similar to other types of the moist (wet) wound dressings, it isnecessary to have sufficient information about their dehydration kinetics during thepre-usage period (e.g. storage duration) and also the wound healing process. In thiswork, hydrogel wound dressings based on polyvinyl alcohol were prepared bycyclic freezing-thawing method and their dehydration process investigated byexperimental and mathematical methods. The dehydration tests were performed atatmospheric pressure at 37 °C, using hydrogels containing initial water content of70, 80 and 90 wt% and thickness of 1, 3 and 4 mm. The dehydration kinetics of eachhydrogel was determined by plotting the relative water loss (ratio of water loss toinitial water content) versus time. The obtained results showed that the dehydrationrate has inverse dependency to the thickness of wound dressing. On the other hand,the initial water content of the wound dressing has not significant effect on itsdehydration rate. To compare the obtained results with theoretical data, themathematical modeling on the basis of diffusion mechanism was developed topredict the dehydration process of the wound dressings. The results obtained fromthe mathematical modeling were in agreement with the experimental results showingthat the main phenomenon governing the dehydration of the wound dressings is thediffusion.